2012
DOI: 10.1097/aap.0b013e318269d29e
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetics and Pharmacodynamics of Liposome Bupivacaine Administered Via a Single Epidural Injection to Healthy Volunteers

Abstract: Epidurally administered liposome bupivacaine 266 mg resulted in a longer duration of sensory blockade than liposome bupivacaine 89 or 155 mg or bupivacaine HCl 50 mg. Duration of motor blockade was shorter with liposome bupivacaine 266 mg versus bupivacaine HCl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 14 publications
2
41
2
Order By: Relevance
“…Liposome bupivacaine consists of microscopic, spherical, multivesicular liposomes (DepoFoam 2 drug delivery technology) containing encapsulated bupivacaine 13 . The structure of liposome bupivacaine allows for drug release over several days after administration into the surgical site 14,15 . In published prospective clinical studies in patients undergoing total knee arthroplasty 16 , hemorrhoidectomy 17,18 , breast augmentation 19 , or bunionectomy 20 , a single administration of liposome bupivacaine at the surgical site was well tolerated and associated with lower mean cumulative pain scores, comparable or less opioid consumption, and a comparable adverse event profile compared with bupivacaine HCl or placebo.…”
Section: Introductionmentioning
confidence: 99%
“…Liposome bupivacaine consists of microscopic, spherical, multivesicular liposomes (DepoFoam 2 drug delivery technology) containing encapsulated bupivacaine 13 . The structure of liposome bupivacaine allows for drug release over several days after administration into the surgical site 14,15 . In published prospective clinical studies in patients undergoing total knee arthroplasty 16 , hemorrhoidectomy 17,18 , breast augmentation 19 , or bunionectomy 20 , a single administration of liposome bupivacaine at the surgical site was well tolerated and associated with lower mean cumulative pain scores, comparable or less opioid consumption, and a comparable adverse event profile compared with bupivacaine HCl or placebo.…”
Section: Introductionmentioning
confidence: 99%
“…However, when a single epidural injection of 266 mg DepoFoam formulation was administered to healthy volunteers, prolonged duration of sensory block without extending motor block was observed (18).…”
Section: Several Effects Of Multilamellar Liposome-associated Bupivacmentioning
confidence: 99%
“…Therefore, it is noteworthy that there has been no evidence of myotoxicity or neurotoxicity associated with liposome bupivacaine in clinical studies that have been conducted to date. Further, the study of epidural administration of liposome bupivacaine versus bupivacaine HCl found that subjects who received liposome bupivacaine experienced a longer duration of sensory block with less effect on motor function [33].…”
Section: Risks Of Myotoxicity and Neurotoxicity With Local Anestheticsmentioning
confidence: 99%
“…In addition, dogs treated with bupivacaine HCl or lidocaine/ epinephrine plus liposome bupivacaine exhibited a slight prolongation of activated partial thromboplastin time that was not observed in animals treated with liposome bupivacaine alone. The PK and pharmacodynamics (PD) of epidural liposome bupivacaine were evaluated in a Phase I, randomized, doublemasked, dose-escalating study in 30 healthy volunteers [33]. Sequential cohorts were treated with 89, 155 or 266 mg of liposome bupivacaine or 50 mg of bupivacaine HCl ( Table 1).…”
Section: Epidural Administrationmentioning
confidence: 99%
See 1 more Smart Citation